Regulated expression of a Drosophila melanogaster heat shock locus after stable integration in a Drosophila hydei cell line. - Sinclair, J H (1985)
DNA-mediated cotransformation has been used to transfer a Drosophila melanogaster heat shock locus into cultured Drosophila hydei cells by use of the copia-based selectable vector pCV2gpt and of pMH10A, a cloned 87A7 heat shock locus encoding a mutant heat shock protein (hsp). Transformed lines contain between 50 and 200 copies of both plasmids, each separately organized as a head-to-tail concatemer which is stably maintained in the transformed lines. Exposure of the cotransformants to heat shock temperatures induces the regulated expression of the hsp RNA and the mutant hsp in all the lines analyzed.